Coal miners' wives : portraits of endurance - Giesen, Carol A. B., 1931- (The University Press of Kentucky, 2015)
Few people in America today live with the dangers and deprivations that Appalachian coal mining families experience. But to the eighteen West Virginia women Carol Giesen interviewed for this book, hard times are just everyday life. These coal miners' wives, ranging in age from late teens to eighty-five, tell of a way of life dominated by coal mining -- and shadowed by a constant fear of death or injury to a loved one. From birth to old age, they experience the social and economic pressures of the coal mining industry. Few families in these communities earn their living in any job outside a coal.